The International and Political Journal: Political participation in Iraq after 2003 - Zangeel, Lecturer Dr. Sumaya Ghaleb (The International and Political Journal, 2024)
collective, organized or spontaneous, continuous or interrupted, peaceful or violent, legitimate or not, effective, or ineffective. It is a form of political practice, related to the structure of the political system and the mechanisms of its various operations. Its position within the political system lies in the inputs, whether to provide support to the existing authority or to the opposition, but it aims to change the outputs of the political system, in a way that suits the demands of the individuals and groups to whom it is submitted.